(untitled) (mathematica didactica, 2022)
Hitherto, research on modelling in mathematics classroom rather not refers to philosophical findings on models in science. Therefore, this article connects both, (analytic) philosophy of science and research on mathematics education, and asks for what impact major positions in philosophy of science could have on the discourse on mathematical modelling in the classroom. In particular, the article challenges the separation between mathematics and reality or the “rest of the world” (which is widely shared among researchers on modelling in mathematics classroom) against the background of the syntactic view and the semantic view on models and theories.